Electrospun Inorganic Nanofibers for Oxygen Electrocatalysis: Design, Fabrication, and Progress. Issue 45 (27th October 2020) - Lei, Yongpeng; Wang, Qichen; Peng, Shengjie; Ramakrishna, Seeram; Zhang, Dou; Zhou, Kechao
Abstract: Electrospinning has received tremendous attention in terms of the design and fabrication of 1D nanofibers for oxygen electrocatalysis in fuel cells and metal‐air batteries, owing to their high surface area, short charge transport path, superior chemical stability, etc. In this review, a brief introduction is given for fuel cells, metal‐air batteries, and the operation principle of electrospinning. After that, the recent progress of the noble‐metal‐free electrocatalysts prepared through electrospinning, mainly containing heteroatoms‐doped electrospun carbon nanofibers (ECNFs), ECNFs functionalized with transition metal nanoparticles and their compounds (alloy, oxides, carbides, nitrides, sulfides, phosphides), and unique nanostructured transition metal‐nitrogen‐ECNFs (including single‐atom catalysts) are summarized. In this section, electrospun electrodes with self‐standing peculiarity are emphasized. Next, other kinds of electrospun nanofibers based on oxides, nitrides, and carbides as electrocatalysts or their hybrid materials are also discussed. Finally, the prospects and possible future research direction of electrospun NFs‐based oxygen electrocatalysts are also presented. This comprehensive review is anticipated to be valuable and helpful in the context of understanding the design and fabrication of advanced energy conversion and storage devices. Abstract : This review covers the design and fabrication of oxygen electrocatalysts toward metal‐air batteries and fuel cells, prepared through electrospinning, that mainly contain heteroatom‐doped electrospun carbon nanofibers (ECNFs), ECNFs functionalized with transition metal nanoparticles and their compounds (alloy, oxides, carbides, nitrides, sulfides, phosphides), and unique nanostructured transition metal‐nitrogen‐ECNFs (including single‐atom catalysts).